Optical variability of TeV blazars on long time-scales. Issue 4 (4th February 2019) - Gaur, Haritma; Gupta, Alok C; Bachev, R; Strigachev, A; Semkov, E; Wiita, P J; Kurtanidze, O M; Darriba, A; Damljanovic, G; Chanishvili, R G; Ibryamov, S; Kurtanidze, S O; et al.
ABSTRACT: We present the results of photometric observations of three TeV blazars, 3C 66A, S4 0954+658, and BL Lacertae (BL Lac), during the period 2013–2017. Our extensive observations were performed in a total of 360 nights which produced ∼6820 image frames in BVRI bands. We study flux and spectral variability of these blazars on these lengthy time-scales. We also examine the optical spectral energy distributions of these blazars, which are crucial in understanding the emission mechanism of long-term variability in blazars. All three TeV blazars exhibited strong flux variability during our observations. The colour variations are mildly chromatic on long time-scales for two of them. The nature of the long-term variability of 3C 66A and S4 0954+658 is consistent with a model of a non-thermal variable component that has a continuous injection of relativistic electrons with power-law distributions around 4.3 and 4.6, respectively. However, the long-term flux and colour variability of BL Lac suggests that these can arise from modest changes in velocities or viewing angle toward the emission region, leading to variations in the Doppler boosting of the radiation by a factor of ∼1.2 over the period of these observations.